Spatial quality competition - Pontes, José Pedro (1995)
The coexistence of horizontal and vertical product differentiation in a duopoly is modeled through a spatial setting: horizontal differentiation is expressed by the relative locations of firms and consumers in a product space; vertical differentiation is modeled by difference in firms' transport rates. The duopoly is set in the context of a two-stage model, where firms select first qualities(e.g. transport rates) then prices. In opposition to the existing literature in this field (Launhardt (1885), Dos Santos Ferreira and Thisse (1992)), we assume that consumer's reservation price is finite. This change of assumption leads to two desirable outcomes. First, it sets an endogenous lower bound to the firm's quality level, thus making useless the assumption of an arbitrary bound, which otherwise would be needed. Second, horizontal and vertical differentiation are shown to coexist in equilibrium, which fits with. The purposes of the model.